2009
DOI: 10.3109/11038120902730166
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Worker Role Self-assessment instrument used to evaluate unemployed people in Sweden

Abstract: The aim was to determine the psychometric properties of the new Worker Role Self-assessment (WRS) instrument. The content validity, utility, test-retest reliability, sensitivity to change, and predictive validity of the WRS were investigated in two subject samples, which were selected at work and pain rehabilitation clinics, respectively. One of these groups consisted of 23 clients and four occupational therapists, and the other comprised 83 clients. All clients in both samples were unemployed. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…A previous study on the WRS, where the target group was people with mixed problems who participated in vocational rehabilitation, suggested that the WRS could produce ceiling effects (Wastberg et al, 2009). This was, however, not the case in this study of people with psychiatric disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study on the WRS, where the target group was people with mixed problems who participated in vocational rehabilitation, suggested that the WRS could produce ceiling effects (Wastberg et al, 2009). This was, however, not the case in this study of people with psychiatric disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…This meant, for example, that a question regarding the physical environment was excluded, and three WRI items that concern the psychosocial environment were reformulated from addressing the workplace to targeting the larger context of family and support systems. This is described in more detail by Wästberg and colleagues (Wastberg et al, 2009). The WRS was found to have acceptable content and construct validity, utility, internal consistency and 5 test-retest reliability among people with a variety of musculoskeletal or stress-related problems in ongoing work rehabilitation.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations